Unifying themes in complex systems V proceedings of the Fifth International Conference on Complex Systems - Minai, Ali; Braha, Dan; Bar-Yam, Yaneer (Springer complexity, 2010)
The International Conference on Complex Systems (ICCS) creates a unique atmosphere for scientists of all fields, engineers, physicians, executives, and a host of other professionals to explore common themes and applications of complex system science. With this new volume, Unifying Themes in Complex Systems continues to build common ground between the wide-ranging domains of complex system science.